ANALISIS PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI (Survei pada Aparatur Sipil Negara Pengadilan Negeri Surakarta Kelas 1A Khusus) - Febriani, Yani; Wahyudi, Amin; Suprayitno, Suprayitno (Universitas Slamet Riyadi, 2019)
The purposes of this study are to analyze the significance of the effect of leadership and working environment on working satisfaction, analyze the significance of the effect of leadership, working environment and working satisfaction on the State Civil Apparatus Performance and analyze the significance of leadership and working environment on the State Civil Apparatus Performance with working satisfaction as a mediating variable. This type of research is survey research. The population of this study is the State Civil Apparatus Special Class 1A Surakarta District Court as many as 110 people and all of them are used as samples by population research techniques or census. The source of data uses primary data and secondary data. The method of data collection used a questionnaire and literature. Data analysis techniques used path analysis. The results showed that leadership has a significant effect on the work satisfaction State Civil Apparatus. The work environment has a significant effect on the working satisfaction State Civil Apparatus. Leadership has a significant effect on the performance State Civil Apparatus. Work environment has a significant effect on the State Civil Apparatus. Working satisfaction has a significant effect on State Civil Apparatus. Work satisfaction mediates the effect of leadership on State Civil Apparatus. Work satisfaction mediates the effect the work environment on the State Civil Apparatus.